Diet quality indices and odds of metabolic dysfunction-associated fatty liver disease: a case-control study - Ramaiah, Pushpamala; Jamel Baljon, Kamilya; Alsulami, Sana A.; Lindsay, Grace M.; Chinnasamy, Lathamangeswari (Frontiers in Nutrition, 2024)
Objectives: There are only limited studies investigating the impact of dietary quality indicators, such as dietary quality indices (DQI), dietary diversity score (DDS), and alternative healthy eating index (AHEI), on metabolic dysfunction-associated fatty liver disease (MASLD). Furthermore, these indicators may have different components that could lead to varying results. Therefore, this study aims to assess the nutritional quality indicators and their potential association with MASLD.The study included 128 recently diagnosed MASLD patients and 256 controls aged between 20 and 60 years. The participants' dietary intake was evaluated using a validated semiquantitative food frequency questionnaire that consisted of 168 items. The method used to evaluate dietary diversity in this study was based on five main food groups, specifically bread and grains, vegetables, fruit, meat, and dairy. The AHEI-2010 was computed using data collected from the FFQ.Results: After adjusting for confounders in the fully adjusted model, a significant negative correlation was observed between DDS and the risk of MASLD (OR 0.41, 95% CI 0.20, 0.97).Participants in the top quartile of AHEI had a 76% lower risk of MASLD compared to those in the bottom quartile after controlling for all potential confounders in the fully adjusted model (OR 0.24, 95% CI 0.12, 0.56).The results of our study suggest that there is a significant association between adherence to a high diversity diet and a reduced likelihood of developing MASLD. Similarly, we observed a similar association between adherence to the AHEI diet and a lower risk of MASLD.